LncRNA TUG1 Regulates Proliferation of Cardiac Fibroblast via the miR-29b-3p/TGF-β1 Axis - Guo, Yini; Sun, Zongli; Chen, Minghe; Lun, Junjie (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) is a very common clinical arrhythmia, accompanied by the over proliferation of cardiac fibroblasts (CFs). This study aimed to investigate the role of long noncoding RNA (lncRNA) Taurine upregulated gene 1 (TUG1) in proliferation of CFs, and further investigated its underlying mechanism. Methods: 104 paroxysmal AF patients and 94 healthy controls were recruited. Human CFs were applied to establish an AF cell model through treatment with angiotensin II (AngII). qRT-PCR was used for the measurement of gene levels. The cell proliferation was detected by cell counting kit-8 (CCK-8). Luciferase reporter assay was performed for target gene analysis. Results: Elevated levels of TUG1 and low expression of miR-29b-3p were detected in the serum of AF patients compared with the healthy controls. Pearson’s correlation analysis exhibited an inverse relationship between TUG1 and miR-29b-3p expression in AF patients (r =-7.106, P < 0.001). Knockdown of TUG1 inhibited AngII induced CFs proliferation. TUG1 functions as a competing endogenous RNA (ceRNA) for miR-29b-3p, and downregulation of miR-23b-3p reversed role of TUG1 in CFs proliferation. TGF-β1 is a direct target gene of miR-29b-3p. Conclusions: LncRNA TUG1 is a key regulator in the occurrence of AF. Slicing TUG1 inhibits CFs proliferation by regulating miR-29b-3p/ TGF-β1 axis.